ANALISIS DATA PANEL PADA KINERJA REKSADANA SAHAM - I Gede Agus Astapa; Gede Suwardika; I Ketut Putu Suniantara (Universitas Bumigora, 2018)
Mutual funds is another investment opportunity with a more measurable risk as well as return high enough with enough capital is affordable for the community. Mutual fund performance can be measured by several indicators.. Modeling the performance of mutual funds modeled by regression of the data panel. The regression model estimation data panel will do with the three approaches, namely the approach of common effect, fixed effects and random effects. This research purpose to know the performance of mutual funds from stock selection skill variable influences, market timing ability and level of risk with the use of panel data analysis. The results shows that the Fund's performance is affected by the stock selection skill, market timing ability, and the level of risk. Model the right approach to model the performance of mutual funds by using a random effects model.